2014
DOI: 10.1139/cjes-2013-0220
|View full text |Cite
|
Sign up to set email alerts
|

Brown bear (Ursus arctos) (9880 ± 35 BP) from late-glacial Champlain Sea deposits at Saint-Nicolas, Quebec, Canada, and the dispersal history of brown bears

Abstract: A bear third metatarsal was discovered in Champlain Sea deposits at the Saint-Nicolas site, Quebec. It is identified morphologically probably as a brown bear (Ursus arctos) based on the combination of morphology and ancient DNA. It is the first evidence of bears from Champlain Sea deposits. This bone was radiocarbon dated by accelerator mass spectrometry (AMS) to 9880 ± 35 BP (radiocarbon years BP, taken as 1950) -close to the end of the Champlain Sea phase in eastern North America. The specimen is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Similarly, we found that the 11.3 cal. ka BP (Harington et al 2014) brown bear bone recovered from Champlain Sea deposits in QuŽbec, Canada (Fig. 1) has at least 8.5% (Z=5.7) polar bear ancestry (supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we found that the 11.3 cal. ka BP (Harington et al 2014) brown bear bone recovered from Champlain Sea deposits in QuŽbec, Canada (Fig. 1) has at least 8.5% (Z=5.7) polar bear ancestry (supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the geographic extent of potential admixture between brown bears and polar bears, we also extracted and analyzed DNA from an 11.3 cal. ka BP (Harington et al 2014) brown bear bone from the coast of the Champlain Sea in QuŽbec, Canada, and from two brown bears from the present-day population of Kunashir Island, in eastern Russia (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…ka BP (Harington et al 2014) brown bear bone recovered from Champlain Sea deposits in Quebec, Canada ( Fig. 1) has at least 8.5% (Z=5.7) polar bear ancestry (supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the geographic extent of potential admixture between brown bears and polar bears, we also extracted and analyzed DNA from an 11.3 cal. ka BP (Harington et al 2014) brown bear bone from the coast of the Champlain Sea in Quebec, Canada, and from two bears from the present-day population of Kunashir Island, in eastern Russia ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, large-scale range expansion during glacial periods is evident in the fossil record of vertebrates in extra-Arctic regions [81]. For example, the post-glacial Champlain Sea (13-9 ka, [159]) of New York, Vermont, and Canada has well-studied Arctic vertebrate faunas that include whales, walruses, brown bears and seals [64,83]. Likewise, in coastal regions around Alaska, fossil records [31, 85] support molecular genetic data [23] showing that during the LGM, polar bears and ringed seals ranged as far south as the Gulf of Alaska, considerably south of their current Arctic ranges.…”
Section: Arctic Ocean Marine Mammalsmentioning
confidence: 99%